PI3K-CCL2-CCR2-MDSCs axis: A potential pathway for tumor Clostridia-promoted CD 8+ T lymphocyte infiltration in bile tract cancers - Wen-Jie Ma; Zheng-Hua Li; Zhen-Ru Wu; Fei Liu; Jun-Ke Wang; Yu-Jun Shi; Yan-Wen Jin; Fu-Yu Li (Neoplasia: An International Journal for Oncology Research, 2023)
Background: Most patients with resected bile tract cancers (BTCs) survive for less than 5 years; however, some achieve better prognosis. The tumor microbiome can improve survival by regulating the tumor immune microenvironment. However, whether the tumor microbiome promotes immune cell infiltration in BTCs is unknown. This study aimed to determine the association between CD8+ T lymphocyte infiltration and the tumor microbiome in patients with resected BTCs. Methods: Archived formalin-fixed paraffin-embedded tumor specimens were collected from patients with resected BTCs and analyzed using 16S rRNA gene sequencing to identify that prognosis-related and significantly differentially enriched taxa. Gene ontology (GO) analysis of the differentially enriched taxa was used to assess how CD8+ T lymphocyte infiltration is affected by the tumor microbiome of BTCs. Results: We enrolled 32 patients with resected BTCs. The high CD8+ lymphocyte-infiltration (CD8hi) group had four significantly enriched taxa, and in the low CD8+ lymphocyte-infiltration (CD8low) group comprised one significantly enriched taxon. Patients with higher Clostridia abundance (enriched in the CD8hi group) experienced longer overall survival than those with lower abundance. The enrichment of Clostridia in the CD8hi group corresponded with lower CCL2 expression and downregulation of phosphatidylinositol 3-kinase activity, which might decrease myeloid-derived suppressor cell recruitment to the tumor milieu, thus increasing CD8+ lymphocyte infiltration in BTCs. Conclusions: The tumor microbiome is related to CD8+ T lymphocyte infiltration in patients with resected BTCs. The relationship between tumor Clostridia and high infiltration of CD8+ T lymphocytes might reflect decreased recruitment of myeloid-derived suppressor cells via the PI3K-CCL2-CCR2 axis.